COMMUNICATION STRATEGIES IN CONVERSATION USED BY INTROVERT STUDENTS AT POLITEKNIK LP3I MEDAN - Sarah Monalisa Harahap; Anni Holila Pulungan; Siti Aisyah Ginting (LINGUISTIK TERAPAN, 2021)
This study deals with the language  communication strategies in conversation used by extrovert and introvert students at Politeknik LP3i Medan. It uses qualitative research design with a single case study to gain an understanding on this study. It is conducted descriptively. This study aims to find out the types of communication strategies in conversation used by introvert students of Politeknik LP3i Medan. The subjects were 10 persons of introvert and of Politeknik LP3I Medan. The use of instruments in this study were observation ,interview and documentation. The observation were the types of communication strategies in conversation used by extrovert and  introvert students of Politeknik LP3i Medan. The interview was used to in depth the data. The theories of Celce-Murcia was used in this study. The data were analyzed by Spradley (1979) analysis. The result of the study there were three reason of communication strategy were used by students of Politeknik LP3I Medan. They are providing opportunities for practice strategy, proving list of needed vocabulary and remind forgotten words strategy.Keywords: Communication Strategies, the Reason Why the Introvert Students Used Communication Strategies in the Way They Do